(untitled) (Research, Society and Development, 2022)
This study analyzed the scientific evidence of the emotional repercussions of the work of the nursing team in pre-hospital care, with stress being a direct influence on everyone’s professional life, which can cause a rupture in the internal balance of the organism. Work overload, inadequate resources, salary and professional devaluation along with several other factors can culminate in the psychological risk of professionals, which can be observed mainly in emergency rooms. In this context, exposure to stressful conditions, the accumulation of functions and specificities of work can trigger states of stress and interfere with work, health and quality of life of the professional. Therefore, this research adopted a literature review with a qualitative approach, in order to understand the emotional repercussions related to the activities of the nursing team. To carry out the research, the following databases were used: LILACS, MEDLINE, Academic Google, SciELO and the Virtual Health Library. This research identified 16 relevant articles, after full reading, 10 were excluded, after which 6 articles were selected for this review. In this way, the literature review shows, based on the articles identified, the themes that covered the conditions and exposure of the nursing team in their work activity, as the causative factors that cause damage to this professional, which makes it essential to apply measures that can mitigate these damages.